Exploring symmetry concepts through Hindu's weeding rituals: Ethnomathematics and ethnomodelling perspectives - Parajuli, Kharika; Koirala, Bidya Nath Koirala (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2025)
This study explores the concepts of geometric symmetry embedded in Hindu marriage ritual activities. A community-based descriptive ethnographic approach was employed in a Hindu-majority community in Pokhara, Kaski District, using local participants’ experiences and the researchers’ lived observations. Data were collected through observations, field notes, photographs, videos, and reflective insights, and analyzed using a data reduction process to generate meaningful themes. The findings reveal that Hindu marriage rituals incorporate diverse symmetry concepts and properties, including vertical and horizontal lines of symmetry, infinite lines of symmetry, as well as rotational and translational symmetry. These forms of symmetry align with key topics taught in school geometry. The results demonstrate that mathematical ideas, particularly geometric symmetry, naturally emerge from traditional cultural practices, supporting culturally responsive teaching and learning. Integrating Hindu ritual practices into classroom instruction can enhance students’ and teachers’ conceptual understanding through visualization and contextualization, while providing accessible and well-designed learning resources. Furthermore, such integration promotes creativity, critical thinking, and entrepreneurial skills, contributing to engaging and meaningful learning experiences. The study highlights a strong connection between cultural traditions and formal geometric concepts, and have practical implications for teachers, students, and policymakers in developing context-based teaching strategies, curriculum reforms, and professional development programs.